Determining The Location of The Earthquake Shelter Evacuation In School - Rahmawati, Fauzia; Moch Isya, Hardien Raka (Universitas Pendidikan Indonesia, 2022)
This study aims to analyze the typology of earthquake areas and find suitable locations to serve as evacuation shelters in school for the Lembang fault earthquake disaster in the districts of Padalarang, Ngamprah, Cisarua, Parongpong, Lembang, Cimenyan and Cilengkrang. The method used in this research is descriptive exploratory method which includes measurements and observations in this study. Location was focused by school and the suitable place. The data processing and analysis techniques used were overlay, buffer, querry and marking using the GIS method. The results of this study are; the distribution of typology of earthquake- prone areas of the Lembang Fault is typology A, B and C; and locations suitable for refugee camps are scattered in seven sub-districts and 63 villages, of which there are three villages that do not have suitable refugee locations, namely the villages of Pasirhalang, Kertamulya and Sukatani because their land is densely populated with settlements and lack of land to accommodate residents. is in his village. The proposed evacuation shelter location also adjusts the location of the resident's domicile. The school in that area was suitable for disaster shelter.